Climate Change and Energy Technologies in Undergraduate Introductory Science Textbooks. Issue 6 (18th August 2018) - Yoho, Rachel A.; Rittmann, Bruce E.
ABSTRACT: Global climate change and the implementation of energy technologies are among the most pressing issues facing society and the environment today. Related educational content spans the science disciplines. Through an analysis of introductory-level university textbooks from four major US publishers in Biology, Chemistry, and Physics, this study presents trends in terminology and content. As the defining terms, "global warming" and "climate change" are used nearly equally. However, the first location of a working definition for climate change appears earlier. Energy technologies, climate change, and related environmental issues are found, on average, on ≤4% of textbook pages, and variation is large among individual textbooks. Discipline-based trends exist, especially for the energy technologies presented. Addressed separately as a non-renewable, non-fossil fuel, nuclear energy is found on ≤1% of textbook pages and unfavorably represented. The discussion within these science disciplines has implications on introductory-level education, public perception of science, and informed citizenship.